PENGARUH PEMBIAYAAN UMKM DAN RASIO KEUANGAN TERHADAP PERTUMBUHAN LABA BANK UMUM SYARIAH DI INDONESIA - Ghaida Fathihatu Sabila; Fajar Mujaddid (Universitas Muhammadiyah Prof Dr Hamka, 2018)
The aims of this research is to analyze the influence of sharia financing by the real sector through micro, small, and medium enterprises (SMEs), the influence of capital adequacy (CAR), efficiency (BOPO) and the influence of Non Performing Financing (NPF) of Islamic Banking in Indonesia to earn profit in the period 2013-2017 per-quarter. This research using panel data regression method. The result shows that the Capital Adequacy Ratio (CAR) has no effect on profitability (ROA), while SMEs, Efficiency (BOPO) and Non- Performing Financing have a negative and significant effect on the probability of sharia banking. Keywords: Profitability (ROA), Capital Adequacy Ratio (CAR), Efficiency (BOPO), Non-Performing Financing (NPF).